Recovery of degraded pasture by the maize intercropping with Urochloa brizantha cv. Marandu and pigeon pea - Silva, Alex da; Sousa Santos, Fenelon Lourenco de; Mattos Barretto, Vitor Correa de [UNESP]; Freitas, Roberto Jose de; Kluthcouski, Joao (Univ Estadual Mato Grosso Sul, 2018)
The objective of this work was to evaluate the feasibility of the recovery of degraded pastures with the seed bank present in the area, using the maize + pasture + pigeon pea integrated system. The experimental design was a randomized complete block design in a 2x3 factorial scheme composed of the use of pigeon pea and three forage seeding densities (seed bank, 0 kg ha(-1), 2 kg ha(-1) and 4 kg ha(-1)), with 4 replicates. The number of spikes per plant, height of insertion of the first spike, plant height, number of rows per spike, number of grains per row, weight of one hundred grains, maize grain yield, maize fresh mass yield, dry mass yield of maize, Urochloa brizantha cv. Marandu, and pigeon pea. The results demonstrate that the seeds present in the seed bank of the degraded areas are viable to recover the pasture through the consortium. The use of pigeon pea increases forage production up to the seeding density of 2 kg ha(-1) of forage. The use of the maize, brachiaria and pigeon pea integrated does not cause damage to the maize crop in relation to its production components.
Keywords: seed bank; Integration Crop Livestock; Cajanus cajan